New particle formation in the free troposphere: A question of chemistry and timing - Bianchi, F.; Tröstl, J.; Junninen, H.; Frege, C.; Henne, S.; Hoyle, C. R.; Molteni, U.; Herrmann, E.; Adamov, A.; Bukowiecki, N.; Chen, X.; Duplissy, J.; et al. (Science (American Association for the Advancement of Science), 2016)
New particle formation (NPF) is the source of over half of the atmosphere's cloud condensation nuclei, thus influencing cloud properties and Earth's energy balance. Unlike in the planetary boundary layer, few observations of NPF in the free troposphere exist. We provide observational evidence that at high altitudes, NPF occurs mainly through condensation of highly oxygenated molecules (HOMs), in addition to taking place through sulfuric acid–ammonia nucleation. Neutral nucleation is more than 10 times faster than ion-induced nucleation, and growth rates are size-dependent. NPF is restricted to a time window of 1 to 2 days after contact of the air masses with the planetary boundary layer; this is related to the time needed for oxidation of organic compounds to form HOMs. These findings require improved NPF parameterization in atmospheric models.